Volunteer Veterans and Entangled Cultures of Victory in Interwar Yugoslavia and Czechoslovakia. (October 2019) - Newman, John Paul
Czechoslovakia and Yugoslavia were two successor states of the Austro-Hungarian empire at great pains in the interwar period to portray themselves, both domestically and internationally, as 'victor states' of the First World War, even though both states inherited societies that were deeply fractured by the experience of war. The symbol of the pro-Entente war volunteer was an important part of both states' interwar cultures of victory. Such volunteers represented just a fraction of war veterans in both countries, but they were given great prominence in their respective state-forming cultures. This article is a study of the origins and the nature of this important entanglement. It begins by defining the problematic nature of the 'culture of victory' in the region, before going on to explore the common origins of the volunteer movements in the wartime pro-Entente émigré groups. It then moves on to a discussion of consequences of the privileging of volunteer veterans in the institutional, political, and commemorative cultures of the two states.